2017
DOI: 10.1590/1983-21252017v30n310rc
|View full text |Cite
|
Sign up to set email alerts
|

Polycultures of Coriander, Carrot, and Arugula in Strip-Intercropping System

Abstract: -The objective of this research was to evaluate combinations of cultivars of coriander and arugula in two croppings with cultivars of carrot in a strip-intercropping system. The study was conducted from November 2014 to March 2015. The experimental design was a randomized complete block in a 2 x 2 x 2 + 2 factorial scheme, with four replications. The treatments consisted of the combination of two cultivars of coriander (Verdão and Português) with two cultivars of carrot (Brasília and Esplanada) and two cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In view of this, the Folha Larga arugula is preferred in relation to the others for cultivation in the Brazilian Cerrado. This same recommendation was made by Cunha et al (2013) for the edaphoclimatic conditions of Chapadão do Sul-MS. Linhares et al (2017) also found good performance of this genotype in concert with carrot and coriander in Mossoró-RN. However, it is worth mentioning that more research should be carried out with these genotypes and others on the market for conclusions about and recommendations for greater certainty.…”
Section: Resultsmentioning
confidence: 60%
“…In view of this, the Folha Larga arugula is preferred in relation to the others for cultivation in the Brazilian Cerrado. This same recommendation was made by Cunha et al (2013) for the edaphoclimatic conditions of Chapadão do Sul-MS. Linhares et al (2017) also found good performance of this genotype in concert with carrot and coriander in Mossoró-RN. However, it is worth mentioning that more research should be carried out with these genotypes and others on the market for conclusions about and recommendations for greater certainty.…”
Section: Resultsmentioning
confidence: 60%
“…Each experimental plot had a total area of 1.44 m 2 (1.20 m x 1.20 m), containing 72 beet plants, spaced 0.20 m x 0.10 m apart. The harvest area of each plot (Linhares et al, 2017) was 0.80 m 2 (1.00 m x 0.80 m), containing 40 beet plants (Fig. 4).…”
Section: Experimental Procedure Treatments and Plant Materialsmentioning
confidence: 99%
“…This species has nitrogen content of 26.2g kg -1 in dry matter, and a carbon/nitrogen ratio of 17/1 at the phenological stage of 126 days after emergence [14]. Countless works in the organic production of vegetables have been developed with this species [15][16][17][18], as well as [19].…”
Section: Original Research Articlementioning
confidence: 99%